Nickel toxicity in wood frog tadpoles: Bioaccumulation and sublethal effects on body condition, food consumption, activity, and chemosensory function. (30th July 2018) - Klemish, Jaimie L.; Bogart, Sarah J.; Luek, Andreas; Lannoo, Michael J.; Pyle, Greg G.
Abstract: Nickel (Ni) concentrations in aquatic ecosystems can be amplified by anthropogenic activities including resource extraction. Compared with fish and invertebrates, knowledge of Ni toxicity in amphibians is limited, especially for northern species. We examined the effect of Ni on wood frog ( Lithobates sylvaticus ) tadpoles, the species with the widest and most northern distribution of any anuran in North America. Wood frog tadpoles were exposed to a Ni concentration gradient (0.02–5.5 mg/L of Ni at 164 mg/L as CaCO3 water hardness) for 8 d and examined for lethality, Ni bioaccumulation, and several sublethal endpoints including body condition, food consumption, activity, and chemosensory function. Nickel induced a sublethal effect on body condition (8‐d 10 and 20% effect concentrations [EC10 and EC20] of 1.07 ± 0.38 and 2.44 ± 0.51 mg/L of Ni ± standard error [SE], respectively) but not on food consumption, activity, or chemosensory function. Nickel accumulation in tadpole tissues was positively related to an increase in aqueous Ni concentration but was not lethal. Both the acute and chronic US Environmental Protection Agency water quality guideline concentrations for Ni (0.71 and 0.08 mg/L at 164 mg/L as CaCO3 water hardness, respectively) were protective against lethal and sublethal effects in wood frog tadpoles. In the present study, wood frog tadpoles were protected by current water quality guidelines for Ni and are likely not as useful as other taxa for environmental effects monitoring for this particular metal. Environ Toxicol Chem 2018;37:2458–2466. © 2018 SETAC Abstract : The body condition of wood frog tadpoles decreases with an increase in the accumulation of nickel (Ni) in the whole body.